DECREASING SCRATCH DEFECTS WITH QCC METHODS ON THE LINE ASSEMBLY FRAME OF THE MOTORCYCLE UNIT IN PT.XYZ - Nelfiyanti Nelfiyanti; Casban Casban; Ridwan ridwan (Universitas Ahmad Dahlan Indonesia, 2020)
PT.XYZ operates in the field of two-wheeled vehicle manufacturing. A product defect is produced in the design, namely scratch defect, which has an average defect percentage of 2.39%, which exceeds the Company's defect standard of 0.2%. This study aims to determine the factors that cause scratch defects and reduce scratch defects using the QCC method on the frame assembly line section. The research method is done with the stage starting from the problem identification stage to find out the problems that need improvement steps. Data collection techniques are done by conducting direct observations in the field and conducting interviews with related personnel as well as performing literature studies to learn the science of literature that has a direct relationship with the research topic. The problem formulation level is done to find out the main problems that are the source of the occurrence of defective products. Stages of activity collecting data obtained based on direct observation results and company defect data. The data processing stage was done using the QCC method with PDCA approach and using 5W + 1H stage for the repair process so that the defect value is 0.56%, in this case, there is a decrease in the percentage of a defect by 1.84% from the previous 2.39%. As well as giving a good quality influence on the products produced